METODE DAN STRATEGI PENINGKATAN KUALITAS TAHFIDZ QUR'AN SANTRI DI PONDOK MASARAN TAHUN PELAJARAN 2022/2023 - Istiqomah, Fajar; Subando, Joko; Abbas, Ngatmin (Al’ulum Jurnal Pendidikan Islam, 2024)
The purpose of this study was to analyze the methods and strategies for increasing the memorization of the Koran at the Tahfidzul Qur'an Ar Rabbani Islamic Boarding School and the Tahfidzul Qur'an Muhammadiyah Darul Hikmah Masaran Islamic Boarding School. This study can provide valuable insights for managers and stakeholders of the tahfidz Islamic boarding school to improve the quality of students' Qur'anic education with the aim of increasing the effectiveness and efficiency of Pondok Masaran. This study used a qualitative approach with descriptive methods carried out in the field by collecting information from school principals, supervisors (musyrif) and students through observation, interviews, questionnaires and documentation. Data were analyzed descriptively using data manipulation, display and inference. The main method used is “recitations” (recitation of the Qur'an over and over again) coupled with additional methods such as memorizing the end of verses and the combined approach. Strategies focus on repetition, "murojaah" (revision), and understanding the meaning of verses to strengthen memorization. Teacher support and proper time management drive success. Even if there are obstacles such as lack of motivation and difficulty remembering, a change in strategy can overcome them.